Taxation and international trade dynamics in Nigeria: A VECM analysis - Kabir, Aishatu; Rasheed, Nasir Bukola (American Journal of Social Sciences and Humanities, 2026)
This study examines the impact of taxation on international trade dynamics in Nigeria from 2011Q1 to 2024Q4. The purpose of the study is to analyze how key tax instruments influence export and import performance within the Nigerian economy. The study adopts a Vector Error Correction Model (VECM) to examine the long-run and short-run relationships between taxation and trade flows, while innovation accounting analysis is employed to assess the dynamic effects of tax shocks on exports and imports over time. The findings indicate that positive shocks to customs duties temporarily boost exports and imports when aimed at revenue mobilization but may reduce exports and generate cyclical effects on imports when used for trade control purposes. Corporate income tax shocks are found to reduce exports under revenue-driven policies and consistently depress imports, while import-VAT shocks have a detrimental effect on both export and import flows. In the long run, customs duties remain a significant driver of trade dynamics, whereas corporate income tax and import-VAT continue to constrain export and import activity. These results highlight the complex interaction between taxation and trade performance in Nigeria’s external sector. The study therefore recommends that policymakers design tax policies that balance revenue mobilization with trade promotion objectives, incorporate sector-specific considerations, and closely monitor the interaction between trade taxation, investment behavior, and exchange rate dynamics in order to sustain external sector stability and support long-term trade competitiveness.